A randomized controlled trial of vaginal progesterone for luteal phase support in modified natural cycle – frozen embryo transfer. (2nd September 2021) - Horowitz, Eran; Mizrachi, Yossi; Finkelstein, Maya; Farhi, Jacob; Shalev, Amir; Gold, Eran; Raziel, Arieh; Weissman, Ariel
Abstract: Objective: Our aim was to study whether luteal phase support (LPS) increases the live-birth rate (LBR) in women undergoing modified natural cycle (mNC) frozen-thawed embryo transfer (FET). Methods: In a randomized controlled trial, conducted at a university-affiliated tertiary medical center, a total of 59 patients aged 18–45 years, underwent mNC-FET. FET was performed in mNC following ovulation triggering by hCG. Patients were randomized into two groups; The No-LPS Group included 28 women who did not receive LPS, and the LPS Group included 31 women who received vaginal progesterone for LPS. The main outcome measure was LBR. Results: Baseline demographic and clinical characteristics were comparable between the study groups. The no-LPS group and the LPS group did not differ with regard to clinical pregnancy rate (21.4% vs. 32.3%; respectively, p  = .35), LBR (17.9% vs. 19.4%; respectively, p  = .88), or spontaneous miscarriage rate (3.6% vs. 12.9%; respectively, p  = .35). On multivariate logistic regression analysis, LPS was not associated with LBR after controlling for confounders. Conclusion: The results of our study suggest that LPS after mNC-FET does not improve the reproductive outcome, and therefore, might not be necessary.C linicaltrials.gov identifier: NCT01483365.